A potential effect of rh-BMP2 on P53 gene expression in the proceeding oral squamous cell carcinoma In Hamsters - khaled zaid; charif barakat; rashad murad; nour abou qersh; mansour chantiri (Asian Pacific Journal of Cancer Biology, 2017)
Bone morphogenetic proteins (BMPs), belonging to the transforming growth factor-β superfamily, regulate many cellular activities. The Use of recombinant human bone morphogenic protein‑2 (rhBMP‑2) in oral and maxillofacial surgery has seen a tremendous increase, yet the relation between rh-BMP2 and oral squamous cell carcinoma cells (OSCC) is not fully clear. This study aimed to investigate the effect of rh-BMP2 on p53, a tumor suppressor gene, which is reported to be the most frequent target for genetic alterations leading to cancer during the progression of OSCC in the golden Syrian hamster Buccal pouches. Materials and methods: Buccal pouches of 34 hamsters were painted with 0.5% DMBA in liquid paraffin three times per week for 14 weeks. 0.25µg of rhBMP-2 were injected in the 1st, 7th and 49th days in the Test group (BMP2 group: 17 hamsters), then biopsies were extracted. Expression of P53 was immunohistochemically investigated in the cancerous tissues. Results: p53 expression was noticed in 33.11% of "BMP2 group" samples and in 23.19% of "control group" samples, a valuable statistical difference was noticed P<0.05between the two groups. Conclusion: 0.25µg of rhBMP-2 affects clearly on p53 expression within OSCC cells. BMPs should not be utilized in the presence of a developed oral cancer till more investigations clarify its fully roles and functions in this type of malignancies.